The ecological adaptability of Sanchezia oblonga to biotic and abiotic stress in urban gardens - Chen, Cong; Peng, Yimin; Liu, Lingling; Cai, Xiaoxia; Cao, Zhiqiao; Mu, Xiaokun; Yan, Danfeng; Wen, Yawen (Frontiers in Ecology and Evolution, 2025)
Sanchezia oblonga is a very important urban garden tree species. In order to investigate the ecological adaptability of S. oblonga against various stresses, this study examined physiological response of S. oblonga to biotic (feeding by the snail Achatina fulica) and abiotic (simulated pruning) independent interference. The changes in malondialdehyde content, catalase activity, and peroxidase activity were assessed over time. Our findings demonstrated that A. fulica significantly damaged S. oblonga, consuming an average of 0.22 ± 0.01 grams per hour. Furthermore, both simulated pruning and snail feeding significantly impacted the levels of malondialdehyde content and the activities of catalase and peroxidase in the plant’s leaves. Compared to the control group, both stresses induced increased malondialdehyde synthesis and heightened catalase and peroxidase activity. Interestingly, both snail feeding and leaf cutting stresses can induce more persistent defense responses in S. oblonga. Additionally, the activity of defense enzymes declined over time following stress exposure, with a more sustained effect observed in the simulated pruning group compared to the snail feeding group. Overall, the study highlights ecological adaptability of plant to biotic and abiotic stresses, emphasizing the crucial roles of malondialdehyde, catalase, and peroxidase in response to adversity and stress in S. oblonga. These findings hold significant implications for breeding programs aimed at improving stress resistance and for developing cultivation practices that optimize the health of garden plants. This study present a new perspective on understanding plant ecological adaptability of plants to biotic and abiotic stress in urban gardens.